Exploring Co-Regulatory Scaffolding Between a Coach and Figure Skater in Practice: A Case Study - Bain, Lisa (Université d'Ottawa / University of Ottawa, 2019)
Self-regulated learning (SRL) processes are frequently used by elite athletes and are thought to be an important factor in the development of expertise (McCardle, Young, & Baker, 2017). Before learners become self-regulated, they must first be co-regulated by a more experienced other (Glaser, 1996), such as an instructor. Scaffolding, a form of co-regulation, has three conceptual characteristics: contingency, fading, and transfer of responsibility (van de Pol & Elbers, 2013). Of the little research done on scaffolding, most studies have been in the education domain with few looking at it in a naturalistic setting. This thesis represented a seminal investigation on the nature of scaffolding in a coach-athlete dyad. It aimed to explore scaffolding using a naturalistic, instrumental case study with an experienced female coach (aged 53, national level) and her competitive male figure skater (aged 15, provincial level) using a concurrent mixed methods design (Creswell, 2003). Data were collected through a) an athlete self-report survey on SRL at the beginning and end of data collection; b) participant observation, field notes, and audio recordings of coach-skater dialogue at 16 practices spread across 5 months of the season; and c) three separate interviews at mid-, late-, and post-season with the coach and skater. Study 1 presents results informed by the skater’s survey and quantitative analyses of audio transcripts. The skater’s self-report of the SRL-SP (Bartulovic, Young, & Baker, 2017) was higher at time two (post-season) compared to time one (mid-season), indicating an increase in SRL. Due to very poor reliability uncovered in pilot work, planned analyses to determine changes in the directionality of coach- and skater-initiated discussion and contingency at various points across the season could not be performed. Study 2 presents the results of thematic analysis (Braun & Clarke, 2006) on the interview data and audio transcript excerpts. Deductive analyses showed it was difficult to identify and describe aspects of the three scaffolding characteristics separately due to their overlapping conceptual definitions, and their interplay during practice. Inductive analyses revealed nuances of scaffolding in sport, including micro- and macro-level co-regulation. Micro-level co-regulation emerged as an important “interface” illustrated by mature coach-skater interactions surrounding practice trials. The interface involved shared and individual expectations for the coach and skater, roles, and described transitory processes relating the co-regulatory interface to the skater’s SRL. Fading in sport differed from the linear model in education with a cyclical pattern of engagement by the coach, returning to refine the skater’s elements if they were incorrect. After integrating and interpreting all the data, the findings suggested scaffolding manifests in unique ways in a sport dyad, with SRL representing a process goal of the interface.
Keywords: Co-regulation; Scaffolding; Dyad